Trading with a plan : a step-by-step guide to developing and using an individual plan for trading shares - Compton, Tony. (Wrightbooks, 2000)
Getting started. Selecting your business structure. Determining your trading style. Fundamental or technical analysis? The tools of the trader. Creating the watch lists. Indicators. Moving averages...